Hollow Spheres Consisting of SnS Nanosheets Conformally Coated with S‐Doped Carbon for Advanced Lithium‐/Sodium‐Ion Battery Anodes. Issue 4 (7th January 2020) - Guo, Weiyuan; Ding, Kang; Mei, Shixiong; Li, Xingxing; Feng, Xiaoyu; Guo, Siguang; Fu, Jijiang; Zhang, Xuming; Gao, Biao; Huo, Kaifu; Chu, Paul K.
Abstract: Although tin sulfide is a promising anode material for lithium‐ and sodium‐ion batteries due to the layered structure and high theoretical capacity, the large volume expansion and poor kinetics have seriously hindered further development and application. In this work, hollow spheres consisting of in situ generated SnS nanosheets (SnS@C HSs) conformally coated with S‐doped carbon are fabricated using polystyrene spheres as the self‐sacrifice template and carbon source. The SnS@C HSs with a large SnS interlayer distance, S‐doped carbon matrix, and hollow structure not only relieve the pressure caused by volume expansion during cycling, but also promote fast transfer of lithium/sodium ions leading to a high pseudocapacitance. The SnS@C HSs have excellent electrochemical properties in both LIBs and SIBs such as high capacity, high rate, and outstanding cycling stability. The use of a self‐sacrifice template is demonstrated to be a convenient and efficient strategy to design and prepare carbon‐coated metal hollow spheres for efficient energy storage and conversion. Abstract : Two for the price of one : Hollow spheres consisting of in situ generated SnS nanosheets (SnS@C HSs) conformally coated with S‐doped carbon are fabricated using polystyrene spheres as the self‐sacrifice template and carbon source. Thanks to the unique structure, the SnS@C HSs exhibit excellent performance for both lithium‐ and sodium‐ion batteries.